Comparing optimization algorithms for conventional and freeform optical design: erratum - Houllier, Thomas; Lépine, Thierry (Optics express, 2019)
We want to acknowledge prior research with a very similar focus to our own which we failed to discover before the publication of our paper.We want to acknowledge prior research with a very similar focus to our own which we failed to discover before the publication of our paper.